2019
DOI: 10.1113/ep088057
|View full text |Cite
|
Sign up to set email alerts
|

Arterial and venous cerebral blood flow responses to long‐term head‐down bed rest in male volunteers

Abstract: In this study, we investigated the whole cerebral haemodynamic response to long-term headdown bed rest (HDBR). We hypothesized that long-term exposure to weightlessness influences cerebral blood flow (CBF) or CBF distribution among cerebral arteries and veins because of the different physiological roles of each cerebral vessel. To test this hypothesis, 10 male volunteers were exposed to −6 deg HDBR for 60 days. Blood flows in the internal carotid artery, external carotid artery and vertebral artery or internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…All studies in the present systematic review reported increased venous distension (venous cross-sectional area), increased venous pressure and decreased or even retrograde venous flow states, in cephalad regions of the body, both in microgravity (Arbeille et al, 2015;Fortrat et al, 2017;Herault et al, 2000;Marshall-Goebel et al, 2019;Martin et al, 2016) and in ground-based analogues (Arbeille et al, 2001;Bleeker et al, 2004;Marshall-Goebel et al, 2016;Moreva, 2008;Navasiolava et al, 2010;Ogoh et al, 2020). These findings may be associated with increased cyclical stretch forces and reduced shear forces, which may lead to a pro-thrombotic state, and thus increased VTE risk in spaceflight.…”
Section: Vessel Injury: Altered Endothelial Function In Microgravitymentioning
confidence: 64%
See 1 more Smart Citation
“…All studies in the present systematic review reported increased venous distension (venous cross-sectional area), increased venous pressure and decreased or even retrograde venous flow states, in cephalad regions of the body, both in microgravity (Arbeille et al, 2015;Fortrat et al, 2017;Herault et al, 2000;Marshall-Goebel et al, 2019;Martin et al, 2016) and in ground-based analogues (Arbeille et al, 2001;Bleeker et al, 2004;Marshall-Goebel et al, 2016;Moreva, 2008;Navasiolava et al, 2010;Ogoh et al, 2020). These findings may be associated with increased cyclical stretch forces and reduced shear forces, which may lead to a pro-thrombotic state, and thus increased VTE risk in spaceflight.…”
Section: Vessel Injury: Altered Endothelial Function In Microgravitymentioning
confidence: 64%
“…Furthermore, ground-based analogues have also been shown to induce decreased venous flow, including DI (Moreva, 2008;Navasiolava et al, 2010), HDT (Marshall-Goebel et al, 2016) and HDBR (Arbeille et al, 2001;Bleeker et al, 2004;Ogoh et al, 2020).…”
Section: Stasis: Altered Venous Flow In Spaceflight (Microgravity)mentioning
confidence: 99%
“…For the first time, our previous study (Ogoh et al., 2020) recently demonstrated a differentiated effect of long‐term bed rest (60 days) among blood flows of cerebral arteries and veins. In particular, the anterior cerebral arterial (ICA) and venous (IJV) blood flows decreased, but the posterior cerebral arterial (VA) and venous (VV) blood flows were well maintained around the baseline value during the HDBR.…”
Section: Discussionmentioning
confidence: 85%
“…Our previous report (Ogoh et al., 2020) demonstrated that the ICA blood flow decreased by the 30th day of HDBR; thereafter, the decreased ICA blood flow returned to the baseline level until the 57th day. This finding indicates that the anterior CBF decreased within 1 month, which is consistent with the finding of middle cerebral artery blood velocity reported in the previous studies during short‐term microgravity of less than 3 weeks (Frey et al., 1993; Sun et al., 2002, 2005; Yao et al., 2001).…”
Section: Discussionmentioning
confidence: 88%
“…Cerebral blood flow is governed by cerebral autoregulation through intricate myogenic, neurogenic, and metabolic mechanisms ( 13,14). Due to the rigid skull, overall cerebral arterial inflow must be perfectly matched beat-to-beat by venous outflow to maintain intracranial pressures (ICP) within life-sustaining range (15)(16)(17). Cerebral arterial flow is narrowly maintained relative to changes in posture, blood pressures, and ICP (22).…”
Section: Marshall-goebel Et Al (2019) Performed a Retrospective Analysis Of Ijv Flow On 11 Astronautsmentioning
confidence: 99%